Agents Involved and Severity of Acute Ocular Exposure Reported at a Poison Control Center. (1st November 2020) - Le Roux, Gaël; Buisset, Adrien; Leruez, Stéphanie; Puskarczyk, Emmanuel; Gohier, Philippe; Descatha, Alexis
ABSTRACT: Purpose: The aim was to identify severity factors useful in the initial management of patients with acute ocular exposure while considering both categories of products involved and circumstances of exposure. Methods: A retrospective study over a one-year period that included patients who benefited from the poison center services for eye exposure to a chemical substance. Results: Within a year, 1582 patients were identified. The sex ratio (M/F) was 0.8. The mean age was 28.5 ± 20.3 years. Among children, those under 4 years represented the most significant age category (n = 277; 50.1%). Exposure to chemicals were mild (n = 1342, 84.8%). Adults over 65 years appeared to be more likely to have severe ocular damage (OR: 4.75; [2.26; 9.98]). Unintentional exposures were the most frequent (n = 1548; 97.8%). Ocular exposure primarily occurred at home (n = 937; 59.2%), and at the workplace (n = 396; 25%) which was associated with a higher risk of severe injury (OR: 2.93 [2.16; 3.97]). Cleaning products accounted for 31.2% of exposure cases (n = 457). Exposure to disinfectants is a risk factor of more severe injuries (OR: 1.48 [1.002; 2.19] p = .0472) whereas pH and severity of injuries were not statistically significant. Conclusions: Our study showed the very wide variety of products involved in ocular exposures. Clinicians should pay attention to factors associated with severe injury, including young and old age, work-related injury, substances such as disinfectants, in addition to previously known factors such as acids and bases.